Expression and regulation of caudal in the lower cyclorrhaphan fly Megaselia - Stauber, Michael; Lemke, Steffen; Schmidt-Ott, Urs (Development genes and evolution, 2008)
The homeobox gene caudal (cad) regulates posterior development in Drosophila. In early embryos, the cad protein (CAD) is expressed in a posterior-to-anterior concentration gradient, which contributes polarity to the developing embryo. The CAD gradient is complementary to and dependent on the anterior pattern organizer Bicoid (BCD), which represses the translation of ubiquitous maternal cad transcripts in the anterior embryo through a direct interaction with the cad 3′ untranslated region (UTR). Here, we show that early embryos of the lower cyclorrhaphan fly Megaselia express the putative cad orthologue Mab-cad throughout the posterior three quarters of the blastoderm but lack maternal transcripts. In transgenic blastoderm embryos of Drosophila, Mab-cad cis-regulatory DNA drives the expression of a reporter gene in a similar pattern, while Mab-cad 3′ UTR fails to mediate translational repression of a ubiquitously transcribed reporter. For another lower cyclorrhaphan fly (Lonchoptera) and two related outgroup taxa of Cyclorrhapha (Empis, Haematopota), we report maternal cad expression in ovarian follicles. Together, our results suggest that BCD is not required for the translational repression of Mab-cad, and that maternal cad expression was lost in the Megaselia lineage.